Unlocking Mysteries: What Do Symbols Reveal About Manggarai Birth Rituals? - Niman, Erna Mena; Darong, Hieronimus Canggung (Komunitas, 2023)
This qualitative study explores the deep meanings associated with symbols found in the birth ceremony of the Manggarai culture. The study used participant observation and interviews with traditional leaders as its main data gathering techniques, with a qualitative design based in symbolic interactionism. Using semiotics and pragmatics theory in conjunction with the data analysis spiral technique, the analysis offers a thorough examination of the meanings of the symbols used in the ceremony in question. The findings highlighted the functions of symbols in the birth rite and the profound social and religious significance they have. As such, the meanings of the symbols serve to communicate religious views and form social relationships. Additionally, the findings shows gender characteristics in these symbolic activities, emphasizing gender-specific roles or representations throughout the birth rite. The results provide insightful information on the cultural diversity and symbolic relationships appear in Manggarai birth customs.